Genetic algorithm‐optimised charge simulation method for electric field modelling of plate‐type electrostatic separators. Issue 1 (1st January 2013) - Abouelsaad, Mohamed M.; Abouelatta, Mohamed A.; Salama, Abd‐Elhadi R.
Abstract : A novel combination of genetic algorithms (GAs) and the charge simulation method (CSM) is proposed for enhancing the computation precision of electric fields associated with plate‐type electrostatic separators; a new recycling technology of electrical and electronics waste. An algorithm is developed to, automatically, arrive at optimal arrangement of the simulating charges and their locations in order to eliminate dependency on user judgment and experience. Accurate results for electric field computation, compared with earlier published techniques, are realised for several design parameters of the separator. Experiments carried out for determination of detachment fields of small metallic particles (steel spheres of radius 0.501 mm) confirmed validity of the numerical simulation. The present work shows that the coupled GA–CSM algorithm can be an efficient and flexible design tool for accurate field computation of electrostatic separation equipment.